The art of happiness : a handbook for living - Bstan-'dzin-rgya-mtsho, Dalai Lama XIV, 1935-; Cutler, Howard C. (New York : Riverhead Books, 1998)
One of the world's greatest spiritual leaders teams up with a psychiatrist to share, for the first time, how he achieved his hard-won serenity and how readers can attain the same inner peace.
Purpose of life: Right to happiness -- Sources of happiness -- Training the mind for happiness -- Reclaiming our innate state of happiness -- Human warmth and compassion: New model for intimacy -- Deepening our connection to others -- Value and benefits of compassion -- Transforming suffering: Facing suffering -- Self-created suffering -- Shifting perspective -- Finding meaning in pain and suffering -- Overcoming obstacles: Bringing about change -- Dealing with anger and hatred -- Dealing with anxiety and building self-esteem -- Closing reflections on living a spiritual life: Basic spiritual values.
Keywords: Religious life -- Buddhism; Happiness -- Religious aspects -- Buddhism; Buddhism -- Doctrines